The Process of Women's Decision Making for Selection of Cesarean Delivery - Mansoureh JamshidiManesh; F Oskouie; Leila Jouybary; Akram Sanagoo (Iran University of Medical Sciences, 2009)
Background and Aim: Although cesarean section has been considered as a way for reducing infant and mother mortality rate, it has been changed to a general dilemma, so that in Iran, cesarean rate is higher than World Health Organization standards. The aim of this study was to discover the process of decision making for selection of cesarean delivery by those whodid not have indication for cesarean.   Material and Method: Twenty six pregnant women, experiencing the third trimester, were selected based on purposeful and theoretical sampling. For access to participants, the researcher referred to one teaching health care centers of Iran University of Medical Sciences and two private offices of gynecology in Tehran, Iran. The data were collected by semi-structured interviews. All data were audio taped and transcribed. Data collection and analysis was performed simultaneously. Constant comparative method was used to analyze data.   Results: The main categories were "fear due to not having knowledge", "being painless, and physical and spiritual peace" and "unpleasant experience of others and their encouragement", "being worry of complications", "inappropriate communication of health care staff", and "the feeling of loneliness and death", "infant's health". Constant analysis of data revealed that women get through for creation balance in order to receipt the best result, process of to consider, making a lawful and to choice.   Conclusion: Attentive to main theme that it is fear of labor and delivery is a physiology phenomenon. It is necessary to encourage methods for relieving pain and fear and for promoting self-esteem in order to make good decision by pregnant women. It is also important to encourage women for vaginal delivery.